(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The introduction of telemedicine services in prison represents a fundamental opportunity to improve healthcare access by inmates and detainees, and thus to enhance the effectiveness of right to health. However, while in the US a number of penitentiaries are already offering remote healthcare assistance, the overall interest towards the development of telemedicine in prison in Europe is still scarce. As for the Italian context, the few attempts made at political level to foster the spread of telemedicine in prison have been ineffective. In addition, initiatives reported in this field are not adequately supported, which is a main hindrance to their stabilization in the routine practice. In this essay, the state-of-the-art in the field is drafted and an overview of the main risks and benefits of telemedicine in prison is provided. A specific attention is paid to the Italian situation, especially in the light of the implications posed by the advent of the health emergency provoked by CoViD-19 outbreak.